Distribution of the Mesozooplankton Community in the Western Ross Sea Region Marine Protected Area During Late Summer Bloom - Sung Hoon Kim; Bo Kyung Kim; Boyeon Lee; Wuju Son; Wuju Son; Naeun Jo; Junbeom Lee; Junbeom Lee; Sang Heon Lee; Sun-Yong Ha; Jeong-Hoon Kim; Hyoung Sul La; et al. (Frontiers in Marine Science, 2022)
The spatio-temporal distributions of the epipelagic mesozooplankton community in the western Ross Sea region marine protected area (RSR MPA) were investigated. Mesozooplankton surveys were conducted in February 2018, January 2019, and March 2020 from an approximate depth of 200 m to address the essential environmental factors influencing the mesozooplankton community structure. Our results showed that the mesozooplankton community of the western RSR MPA could be affected by the various ecological factors, depending on their temporal and spatial variations. The community structure in 2018 was distinguished by its chlorophyll-a (Chl-a) concentration during the summer bloom phase in the late summer. Taxa observed in 2019 were divided into four significantly different groups according to the body size of the community composition. This differentiation could be derived from predation pressure, inducing a trophic cascade. Taxa in the 2020 samples were separated into five different groups based on temperature; during the 2020 survey, the water temperature was low and sea ice covered the whole continental shelf in the Ross Sea. Additionally, comparing the results from the three interannual surveys, although the communities clustered according to the survey period, the continental shelf groups were quite dissimilar despite overlapping geographically. Taken all together, the mesozooplankton community of the western RSR MPA changed according to changes in several ecological factors, such as temperature, Chl-a concentration, and predation pressure. The occurrence of summer blooms and the decline in water temperature mainly regulated the mesozooplankton community structure in the late summer.